Legal Authority of Indonesian National Police in Handling Rally or Demonstrations - Kristianita, Friska (UMPurwokerto Law Review, 2022)
Abstract Demonstrations are a form of expression of opinion, which is the right of every citizen regulated by law. Demonstrations always involve the Police as a law enforcement agency, which participates in controlling and maintaining security. Problems arise in the efforts of the Police in dealing with demonstrations or demonstrations. This study aimed to determine the legality of the Police's authority in handling demonstrations and the police efforts. This study uses a normative juridical research method. The normative juridical research method is carried out through a literature study that examines secondary data. The results of this study are; first, cannot be separated the implementation of rallies from the security of the Police, who have the authority in handling demonstrations, and in terms of handling, the Police are authorized to regulate, maintain the course of rallies and provide supervision to protest participants. Second, how to act in the implementation of the demonstration consists of 3 (three) stages, namely the preemptive stage, the preventive stage, and the repressive stage. Keywords: Handling, Police, Demonstrations Abstrak Unjuk rasa atau demonstrasi adalah bentuk ekspresi berpendapat yang merupakan hak setiap warga negara yang diatur dalam Undang-undang. Unjuk rasa selalu melibatkan kepolisian sebagai lembaga penegak hukum, yang ikut serta dalam melakukan penertiban dan keamanan. Permasalahan muncul dalam upaya kepolisian dalam menangani unjuk rasa atau demonstrasi. Tujuan dari penelitian ini adalah untuk mengetahui legalitas kewenangan kepolisian dalam hal penanganan unjuk rasa dan upaya kepolisian yang dilakukan dalam penanganan unjuk rasa. Penelitian ini menggunakan metode penelitian yuridis normatif. Metode penelitian yuridis normatif dilakukan melalui studi pustaka yang menelaah data sekunder. Hasil dari penelitian ini adalah Pertama, Pelaksanaan unjuk rasa tidak terlepas dari pengamanan pihak kepolisian yang memiliki kewenangan dalam penanganan unjuk rasa dan dalam hal penanganan polisi berwenang untuk mengatur, menjaga jalannya unjuk rasa serta memberikan pengawasan terhadap peserta unjuk rasa. Kedua, cara bertindak dalam pelaksanaan unjuk rasa terdiri dari 3 (tiga) tahap yaitu tahap preemtif, tahap preventif dan tahap represif. Kata Kunci : Penanganan, Kepolisian, Unjuk Rasa.